2013
DOI: 10.1016/j.yfrne.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hypothalamus in mediating protective effects of dietary restriction during aging

Abstract: Dietary restriction (DR) can extend lifespan and reduce disease burden across a wide range of animals and yeast but the mechanisms mediating these remarkably protective effects remain to be elucidated despite extensive efforts. Although it has generally been assumed that protective effects of DR are cell-autonomous, there is considerable evidence that many whole-body responses to nutritional state, including DR, are regulated by nutrient-sensing neurons. In this review, we explore the hypothesis that nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 226 publications
1
15
0
Order By: Relevance
“…Many of the responses to DR appear to be mediated by neuroendocrine and autonomic responses that are largely regulated by the ventromedial hypothalamus (VMH) (Dacks et al, 2013). We characterized gene expression in the context of HD within the VMH (Figure 3), and analyzed a panel of genes that are largely responsive to energy homeostasis (Poplawski et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the responses to DR appear to be mediated by neuroendocrine and autonomic responses that are largely regulated by the ventromedial hypothalamus (VMH) (Dacks et al, 2013). We characterized gene expression in the context of HD within the VMH (Figure 3), and analyzed a panel of genes that are largely responsive to energy homeostasis (Poplawski et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these and other studies have consistently shown that caloric restriction can reduce AD-like pathology and improve cognitive behavior; however, the mechanisms underlying this beneficial effect are not known, but may include reducing cellular stress, altering systemic metabolism, and changing hormonal balance e.g., increased insulin sensitivity (Mattson, 2012). It has been proposed that the hypothalamus has a vital role in the benefits seen with caloric restriction (Dacks et al, 2013). Evidence to support a hypothalamic role include the loss of caloric restriction-mediated anti-tumor effects in NPY knockout mice and mice with lesions of the hypothalamic arcuate nuclei by monosodium glutamate, suggesting the importance of hypothalamic pathways that regulate appetite and systemic metabolism in mediating the beneficial effects of caloric restriction (Minor et al, 2011).…”
Section: Alterations In Hypothalamic Function In Admentioning
confidence: 99%
“…In both C. elegans and Drosophila , altered sensory perception alone may play a role, with specific subsets of sensory, including olfactory and gustatory, neurons influencing lifespan (Alcedo and Kenyon, 2004; Allen et al, 2014; Apfeld and Kenyon, 1999; Ostojic et al, 2014; Waterson et al, 2014). In C. elegans , Drosophila and mice, neural circuits both detect nutrient status and control the responses to it, in mice mediated mainly by the hypothalamus (Dacks et al, 2013). Alterations in the levels of metabolites (Chin et al, 2014), in activity of the nutrient-sensing insulin/IGF signaling network (Johnson et al, 2013; Kenyon, 2010) in C. elegans , of steroid hormone signaling (Thondamal et al, 2014) and, in the mouse, of growth hormone (Johnson et al, 2013; Kenyon, 2010) also play important systemic roles.…”
Section: Introductionmentioning
confidence: 99%